cGMP Signaling and Vascular Smooth Muscle Cell Plasticity - Lehners, Moritz (J Cardiovasc Dev Dis, 2018)
Cyclic GMP regulates multiple cell types and functions of the cardiovascular system. This review summarizes the effects of cGMP on the growth and survival of vascular smooth muscle cells (VSMCs), which display remarkable phenotypic plasticity during the development of vascular diseases, such as atherosclerosis. Recent studies have shown that VSMCs contribute to the development of atherosclerotic plaques by clonal expansion and transdifferentiation to macrophage-like cells. VSMCs express a variety of cGMP generators and effectors, including NO-sensitive guanylyl cyclase (NO-GC) and cGMP-dependent protein kinase type I (cGKI), respectively. According to the traditional view, cGMP inhibits VSMC proliferation, but this concept has been challenged by recent findings supporting a stimulatory effect of the NO-cGMP-cGKI axis on VSMC growth. Here, we summarize the relevant studies with a focus on VSMC growth regulation by the NO-cGMP-cGKI pathway in cultured VSMCs and mouse models of atherosclerosis, restenosis, and angiogenesis. We discuss potential reasons for inconsistent results, such as the use of genetic versus pharmacological approaches and primary versus subcultured cells. We also explore how modern methods for cGMP imaging and cell tracking could help to improve our understanding of cGMP’s role in vascular plasticity. We present a revised model proposing that cGMP promotes phenotypic switching of contractile VSMCs to VSMC-derived plaque cells in atherosclerotic lesions. Regulation of vascular remodeling by cGMP is not only an interesting new therapeutic strategy, but could also result in side effects of clinically used cGMP-elevating drugs.